Mutual influence of stock and scion - Conover, John Alfred (My University, 1898)
Introduction: There have been a great many experiments and observations made on this subject by prominent fruit growers and horticulturists all over the world, and much has already been written upon it. In all hires there are those who discredit what has been said contrary to their own views and this is no exception.
Citation: Conover, John Alfred. Mutual influence of stock and scion. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Fruit Growers; Horticulturists; Experiments; Theses; Manuscripts (documents)